Qualidade percebida em serviços hospitalares: uma avaliação empírica da escala servqual - Pesamosca, Denise Luciane (2022)
Knowing the customer's perception of services is a central theme in market studies. This centrality is due to the fact that high levels of perceived quality are associated with higher levels of loyalty, among other organizational outcomes. As a result, many organizations have implemented quality programs centered on assessments carried out by the users of their services, which is no different for the hospital environment, which is increasingly in a competitive environment. Thus, the present study aimed to evaluate the levels of perceived quality in the hospital services provided by Hospital Ministro Costa Cavalcanti (HMCC) through the SERVQUAL scale, as well as the dimensionality of the scale in the hospital context. Data were collected through a survey and processed with the aid of the JASP software, using exploratory and confirmatory factor analysis to assess the dimensionality of the SERVQUAL scale. Our studies revealed that HMCC has an excellent level of perceived quality.